A COMPARATIVE ANALYSIS OF ROBERT LUDLUM'S THE BOURNE SUPREMACY IN NOVEL AND MOVIE VERSION: A STRUCTURAL APPROACH - NUSADARITA , NOVIANA VESTI (2007)
The study deals with the similarities and differences between The Bourne Supremacy in the novel and the movie version. This research paper is aimed at analyzing the structural elements of The Bourne Supremacy both in the novel and movie version by finding out the similarities and differences between them. The present writer uses the theory of structural elements of novel and movie version. This research paper is conducted by using the following methods. The type of the study is comparing Robert Ludlum's The Bourne Supremacy in the novel and the movie version. The types of data are text of the novel and movie scene. The methods of data collection are library research and observation. The technique of data analysis is descriptive qualitative research. The object of this research is The Bourne Supremacy novel version written by Robert Ludlum and the movie directed by Paul Greengrass. Based on the data that have been collected and analyzed, the writer concludes that similarities of both versions lie on the characters and characterization, setting of place, plot, point of view and theme. The differences lie on limitation characters and characterization, the setting, plot, and point of view. Most events in the movie version are changed because Paul Greengrass changes the plot of the story.